How Do Attitudes and Self-Efficacy Predict Teachers’Intentions to Use Inclusive Practices? A Cross-National Comparison Between Canada, Germany, Greece, Italy, and Switzerland - Sahli Lozano, Caroline; Wüthrich, Sergej; Kullmann, Harry; Knickenberg, Margarita; Sharma, Umesh; Loreman, Tim; Romano, Alessandra; Avramidis, Elias; Woodcock, Stuart; Subban, Pearl (Exceptionality Education International)

GenAI-Tools revolutionieren die Produktentwicklung - Dumitrescu, Roman; Falkowski, Tommy; Hovemann, Aschot; Rasor, Rik (KEM Konstruktion Automation)

Bildungsforschung – Erziehungswissenschaftliche Perspektiven

The association between dairy intake in adolescents on inflammation and risk markers of type 2 diabetes during young adulthood: results of the DONALD study - Hohoff, Eva; Jankovic, Nicole; Perrar, Ines; Schnermann, Maike; Herder, Christian; Nöthlings, Ute; Libuda, Lars; Alexy, Ute (Public Health Nutrition)
Abstract Objective: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, non-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. Design: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on high-sensitivity C-reactive protein, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as Homeostasis Model Assessment Insulin Resistance in an open-cohort study. Setting: Dortmund, Germany. Participants: Data from participants ( n 375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-d weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. Results: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all P > 0·05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all P > 0·05). Conclusions: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette E. (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Transitivity in finite general linear groups - Ernst, Alena; Schmidt, Kai-Uwe (Mathematische Zeitschrift)
It is known that the notion of a transitive subgroup of a permutation group $G$ extends naturally to subsets of $G$. We consider subsets of the general linear group $\operatorname{GL}(n,q)$ acting transitively on flag-like structures, which are common generalisations of $t$-dimensional subspaces of $\mathbb{F}_q^n$ and bases of $t$-dimensional subspaces of $\mathbb{F}_q^n$. We give structural characterisations of transitive subsets of $\operatorname{GL}(n,q)$ using the character theory of $\operatorname{GL}(n,q)$ and interpret such subsets as designs in the conjugacy class association scheme of $\operatorname{GL}(n,q)$. In particular we generalise a theorem of Perin on subgroups of $\operatorname{GL}(n,q)$ acting transitively on $t$-dimensional subspaces. We survey transitive subgroups of $\operatorname{GL}(n,q)$, showing that there is no subgroup of $\operatorname{GL}(n,q)$ with $1<t<n$ acting transitively on $t$-dimensional subspaces unless it contains $\operatorname{SL}(n,q)$ or is one of two exceptional groups. On the other hand, for all fixed $t$, we show that there exist nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on linearly independent $t$-tuples of $\mathbb{F}_q^n$, which also shows the existence of nontrivial subsets of $\operatorname{GL}(n,q)$ that are transitive on more general flag-like structures. We establish connections with orthogonal polynomials, namely the Al-Salam-Carlitz polynomials, and generalise a result by Rudvalis and Shinoda on the distribution of the number of fixed points of the elements in $\operatorname{GL}(n,q)$. Many of our results can be interpreted as $q$-analogs of corresponding results for the symmetric group.

Auswertung der modalen Dämpfung von geführten akustischen Wellen in faserverstärkten Kunststoffplatten - Claes, Leander; Hetkämper, Tim; Zeipert, Henning; Henning, Bernd (22. GMA/ITG-Fachtagung – Sensoren und Messsysteme 2024)

Influence of process variations on clinch joint characteristics considering the effect of the nominal tool design - Zirngibl, C; Goetz, S; Wartzack, S (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Focusing on upcoming challenges in lightweight design, such as increasing emission targets or novel multimaterial connections, versatile applicable and environmentally friendly production technologies are crucial. In this context, mechanical joining technology clinching offers a fast and energy-efficient procedure for assembling sheet metals, being a proper alternative to established joining methods, such as spot welding. However, the design of clinch points is a challenge, which is partly supported by numerical or data-based approaches for optimal tool dimensions assuring proper joint characteristics. While this is usually done for an ideal environment, real joining processes are characterized by multiple inevitably varying parameters, e.g. of the material, which have a significant impact on the quality of clinch points. Therefore, this contribution addresses the current gap by analyzing the effect of parameter variations or uncertainties on the resulting joint characteristics and studying the impact of the nominal tool design. Thus, an efficient meta-model-based variation simulation procedure is proposed and used for analyzing the effect of different tool design configurations and variation scenarios. Based on the results, it was found that varying process parameters have a strong impact on the resulting joint characteristics, whereby the effect significantly depends on the nominal tool design. This reveals the potential for a robust tool design and implies that the nominal tool design and the tolerancing of parameters should be done simultaneously for a reliable virtual joining point design without extensive iterations and physical tests.

Identifying K-12 Students' Approaches to Using Worked Examples for Epistemic Programming - Hüsing, Sven; Sparmann, Sören; Schulte, Carsten; Bolte, Mario (Proceedings of the 2024 Symposium on Eye Tracking Research and Applications)

Students’ academic motivation in relation to peer interactions and social environment considering behavioral problems using the experience sampling method - Knickenberg, Margarita; Zurbriggen, Carmen

Effekte von Peerinteraktionen und des sozialen Umfelds auf die aktuelle Motivation von Schüler*innen - Knickenberg, Margarita; Zurbriggen, Carmen

Certifying the Topology of Quantum Networks: Theory and Experiment - Weinbrenner, Lisa T.; Prasannan, Nidhin; Hansenne, Kiara; Denker, Sophia; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine; Gühne, Otfried (Physical Review Letters)

Adaptives Lernen im inklusiven Unterricht aus der Perspektive von Grund- und Förderschullehrkräften – Ergebnisse aus einer Interviewstudie. Posterpräsentation auf der Herbsttagung 2024 der Arbeitsgruppe Empirische Sonderpädagogische Forschung (AESF). - Löper, Marwin Felix; Knickenberg, Margarita; Kretzer, Theresa; Schulze, Jan Roland; Hellmich, Frank

Die Bedeutung von Peers für die aktuelle akademische Motivation von Schüler*innen unter Berücksichtigung von Verhaltensproblemen - Knickenberg, Margarita; Zurbriggen, Carmen

Schlegels Die Braut in Trauer und die Geschlechterpoetik der 'zivilen Tragödie'. Zur gattungsgeschichtlichen Bedeutung von Schlegels Dramenfragment - Süwolto, Leonie (Johann Elias Schlegel und das Theater. Zwischen Revision und Reform)

Johann Elias Schlegel und das Theater. Zwischen Revision und Reform

Geschlechterpoetik. Gattung und Geschlecht in den Tragödien des 18. Jahrhunderts (Johann Christoph Gottsched, Luise Gottsched, Johann Elias Schlegel) - Süwolto, Leonie (Artes)

Kooperation in inklusiven Schulen - Lütje-Klose, Birgit; Wild, Elke; Grüter, Sandra; Gorges, Julia; Neumann, Phillip; Papenberg, Antonia; Goldan , Janka
Schulische Inklusion kann nur gelingen, wenn tragfähige Kooperationsstrukturen aufgebaut werden. Das Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) zeigt, wie die Bereiche teaminterne und multiprofessionelle Zusammenarbeit sowie Kooperation von Schule und Familie optimiert und miteinander in Verbindung gebracht werden können. Das Praxishandbuch bietet die Grundlagen für die eigenständige Durchführung von umfassenden Fortbildungen, die mit Hilfe umfangreicher Online-Materialien auch in einzelne Module geteilt werden können.

Analyzing Security and Privacy Advice During the 2022 Russian Invasion of Ukraine on Twitter - Schmüser, Juliane; Ramulu, Harshini Sri; Wöhler, Noah; Stransky, Christian; Bensmann, Felix; Dimitrov, Dimitar; Schellhammer, Sebastian; Wermke, Dominik; Dietze, Stefan; Acar, Yasemin; Fahl, Sascha (Proceedings of the CHI Conference on Human Factors in Computing Systems, CHI 2024, Honolulu, HI, USA, May 11-16, 2024)

Decomposing and Measuring Trust in Open-Source Software Supply Chains - Boughton, Lina; Miller, Courtney; Acar, Yasemin; Wermke, Dominik; Kästner, Christian (Proceedings of the 2024 {ACM/IEEE} 44th International Conference on Software Engineering: New Ideas and Emerging Results, NIER@ICSE 2024, Lisbon, Portugal, April 14-20, 2024)